Throwing elbow injury prevention: forearm flexor injury association with medial elbow ulnar collateral ligament injury - Zaremski, J. L.; Pazik, M.; Dean, C. W.; Vijayaraghavan, N.; Fethiere, N. P.; Farmer, K. W.; Horodyski, M. (British Journal of Sports Medicine, 2021)
Background The forearm flexors (FF) are a stabilizing biomechanical aspect of the medial elbow. However, there are no studies investigating the association of concomitant UCL injuries and FF injuries in throwing athletes.